(untitled) (The Research of Medical Science Review, 2025)
Microplastic pollution has emerged as a significant environmental challenge due to its persistence, widespread distribution, and detrimental impacts on ecosystems and human health. Conventional plastic waste management strategies often fail to address the complexities of microplastic degradation, necessitating innovative and sustainable approaches. Among various biological solutions, fungal species, particularly Aspergillus, have demonstrated promising potential in microplastic biodegradation. This review explores the role of Aspergillus species in sustainable plastic waste management, focusing on their enzymatic capabilities, degradation mechanisms, and applications in reducing microplastic pollution.The ability of Aspergillus to produce a diverse range of enzymes, such as esterases, lipases, and oxidases, enables the breakdown of complex plastic polymers into simpler compounds. Key species, including A. niger and A. flavus, have shown significant potential in degrading microplastics under controlled environmental conditions. Factors such as temperature, pH, plastic properties, and co- metabolism with other microorganisms influence the efficiency of Aspergillus-mediated degradation. Furthermore, integrating Aspergillus into bioreactors, composting systems, and bioaugmentation strategies presents practical applications for large-scale waste management.Despite these advancements, challenges remain, including slow degradation rates, potential toxicity of byproducts, and scalability issues. Future research should focus on genetic engineering, omics technologies, and the development of integrated systems to enhance degradation efficiency and address current limitations. By leveraging the enzymatic and ecological versatility of Aspergillus, this review highlights its potential as a cornerstone in sustainable plastic waste management and emphasizes the need for continued innovation in combating microplastic pollution.